Análise hedônica dos preços implícitos de varejo dos serviços de telecomunicação brasileiros - Nunes, Andrey Ribeiro Perez (2018)
This work applies hedonic methodology in the analysis of prices of the main Brazilian retail telecommunication markets: mobile telephony, fixed broadband and pay TV. From the collection of the attributes of the available offers in December 2017, this study maps the properties of the telecommunication offers that significantly drive consumers’ purchasing decisions, also measuring the marginal contribution of these items to final prices. In mobile telephony, the attributes associated with data traffic - such as volume and franchise expiration period - were the main drivers identified. In the context of fixed broadband, the traffic speeds, both upload and download, showed prevalence. For pay TV, content related aspects were found more relevant, like the number of high-definition channels, on-demand programming and the inclusion of premium sports and film channels. In addition, this study identified that brand premiums variables were significant only in the context of fixed broadband, associating such finding with the structural peculiarities of that market.